(untitled) (Journal of Fiber Bioengineering and Informatics, 2021)
Temperature greatly in fluences the choice of clothing type. It is difficult to study the effect of temperature on the performance of a garment and the used fabric, as changes in temperature varies signiwithin a year, a season or even a day. This research paper studied the effect of fabric properties on human thermal comfort under different environmental temperatures. The main methodology entails using a CAD software to simulate clothing thermal comfort value of a garment made of 6 fabric types, then conducting analysis on the simulation results. The results indicate that fabrics perform better within a range of temperature. The further they stray from the range, the smaller the impact of the fabrics on human comfort. The results from the methodology also demonstrates that activity types and temperature greatly affect the comfort value.